Analysis of the Arabic Orthography of Pegon Nusantara in Sumatra: Text, Characteristics, and Meaning - Sarif, Suharia; Talibo, Wiranto; Ibnu Rawandhy N. Hula (Pasca Sarjana IAIN Sultan Amai Gorontalo, 2025)
This study examines the orthography of Arabic Pegon in Sumatra as a form of linguistic and cultural adaptation that reflects the process of Islamization in the Malay world. The research aims to describe the distinctive orthographic features of Pegon in Sumatra and to reveal its cultural and religious implications in shaping the identity of Islamic literacy in Indonesia. Using a descriptive-qualitative method with a library research approach, this study analyzes several Pegon manuscripts such as Hikayat Prang Sabi from Aceh, Sullam al-Mubtadi from Minangkabau, and Jawi manuscripts from Palembang. The results show that Arabic Pegon in Sumatra demonstrates unique orthographic innovations through the addition of letters such as ڤ (pa), چ (ca), ݢ (ga), and ڠ (nga), which represent local phonemes not found in classical Arabic. Pegon not only serves as a linguistic medium but also functions as a symbol of Islamic identity, religious education, and cultural expression. Therefore, Arabic Pegon in Sumatra represents the indigenization of Islam in the archipelago and serves as an intellectual heritage that bridges Arabic literacy with local language and culture.